PENGARUH BIROKRASI, INTERVENSI DAN DUKUNGAN TERHADAP KINERJA SALURAN DISTRIBUSI STUDI KASUS PADA PT. OSRAM INDONESIA CABANG SEMARANG - Joni Indra; Sutopo Sutopo (JURNAL STUDI MANAJEMEN ORGANISASI, 2012)
ABSTRACT Distribution activities (place) are one main problem that a company has to face, beside of price, promotion and product (4p), so the market (society) can accept the product. Company must place its product on the right place, and it means: The nearer the product to the market, the easier the consumer to find and consume it. For that reason, the company must keep a good relationship with the distribution channels because of their role as an intermediary between companies to its customers in all area. We cannot imagine, how difficult a company would be if the company must distribute its product directly by itself in all places. The major concentration of the company to produce good product will be disturbed because its interest was divided between production and distribution. To keep this relationship, the company must aware to see its distributor as a partner (mutual advantage) so that they will find it convenience to distribute the company product. This research adopted result of previous research which have done by Boyle et al., (1995) where he found out that Bureaucracy and Support from company are convenience factors, it means: it has influence in increasing distributors performance. On the other hand, Intervention from company is an inconvenience factor and has negatif impact to distributor performance. The technique of the analysis is using Structural Equation Model (SEM) that is used to examine 3 (three) hypothesis that has been developed. The numbers of sample taken in this research are 100 respondents. The result of the examination shows the positif impact between Bureaucracy and Support toward Distribution Performance and the negatif impact of Intervention toward Distribution Performance. Keywords: bureaucracy; support; intervention; distribution activities; time to market